Screening Virtual Senyawa Turunan Azo-Asetohidrazida sebagai Inhibitor Potensial Alfa-Glukosidase - Muhammad Zulqurnain; Sakti Hidayati Fikriya; Andi Suharman; Annisha Noor Dienna; First Ambar Wati (Acta Chimica Asiana, 2025)
Type 2 diabetes mellitus is a progressive metabolic disorder marked by persistent hyperglycemia resulting from insulin resistance, insufficient insulin secretion, or a combination of both conditions. A potential therapeutic target for treating this illness is the suppression of the alpha-glucosidase enzyme, which is a key regulator of postprandial glucose absorption and carbohydrate metabolism. This work conducted a thorough in silico analysis to evaluate the efficacy of three synthesised azo-acetohydrazide derivatives (designated compounds C, D, and E) as alpha-glucosidase inhibitors. Pharmacokinetic properties and drug-likeness characteristics were evaluated using the SwissADME platform, while molecular docking simulations were conducted with AutoDockTools against the alpha-glucosidase enzyme structure sourced from the Protein Data Bank (PDB ID: 3W37), utilising acarbose as a reference inhibitor. All three compounds adhered to essential drug-likeness criteria, including those established by Lipinski, Veber, and Ghose, and exhibited advantageous physicochemical characteristics, such as appropriate molecular weight, lipophilicity, topological polar surface area, and aqueous solubility. The compounds were anticipated to have significant gastrointestinal absorption and had no ability to penetrate the blood-brain barrier, suggesting a minimal risk of central nervous system damage. Compound E demonstrated the highest binding affinity among the compounds, with a docking score of –7.80 kcal/mol, and formed multiple stabilising interactions within the enzyme's active region, such as hydrogen bonds, hydrophobic contacts, and electrostatic interactions. This study's novelty is the computational discovery of azo-acetohydrazide scaffolds as inadequately investigated chemical entities with potential antidiabetic properties. These findings establish a theoretical basis for continued development and substantiate future endeavours in the synthesis and experimental validation of these molecules. This study validates the efficacy of structure-based drug design in discovering novel alpha glucosidase inhibitors and identifies compound E as a good candidate for further in vitro and in vivo research in type 2 diabetes treatment.